Common Teaching Methods for Vocational Education Teachers in Jordan - Ababneh, Ibrahim Qsaem Mohammad (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the common teaching methods of vocational education teachers in Al- Mafraq Governorate in Jordan through application to a sample of (180) male and female teachers. And a tool for the study was developed consisting of (20) paragraphs, and after making sure of the tool’s sincerity and its stability. The study reached the following results: that professional education teachers use a variety of teaching methods, some of which are traditional and others are modern, noting that (practical presentation style, project method, problem solving method, and method of dialogue and discussion) is the most common among professional education teachers, and that justifications Usage is mainly due to the appropriate occasion of the content of the subject of vocational education, the importance of the appropriate method to develop student discovery skills, and employing the method that makes the student the focus of educational process, and there were no statistically significant differences attributable to gender variations or the educational qualification in Yen differences appeared statistically significant Tazly variable experience on common teaching methods of professional education teachers in favor of the experience category 5-10 years. The researcher recommended a number of recommendations, the most important of which were: holding training courses for vocational education teachers in order to train them on how to choose appropriate teaching methods for the vocational education course, and the need to prepare evidence that shows the steps for teaching the content of the vocational education curriculum for professional education teachers to use when employing modern teaching methods.